The Correlation of Education, Work, and Mother's Age with The Completeness of Basic Immunization in Toddlers at Puskesmas Kuok-Riau in Period of January-June 2013 - Yanasta Yudo Pratama; Sifa Anisa Yaoma; Bambang Edi Susyanto (Faculty of Public Health, Andalas University, 2022)
Immunization prevents some dangerous diseases for children. Completeness of basic immunization is influenced by several factors. This study aims to determine the relationship between education, occupation, and maternal age with the completeness of basic immunization. This type of research is descriptive quantitative analytic with cross sectional method. This research was conducted in July 2013 at the Kuok-Riau Public Health Center. The number of samples is 75 and selected by non-probability sampling. Immunization status at the age of 30, 67.3% completed basic immunization and 32.7% did not complete basic immunization. For mothers aged 30 years, 30.4% completed basic immunization and 69.68% did not complete basic immunization. For mothers with education <9 years, 37.9% did not graduate and 62.1% graduated. For mothers with 12 years of education, 67.4% graduated and 32.6% did not graduate. For working mothers, 68.3% completed and 31.7% did not. Housewives, 41.2% completed and 58.8% did not. The results of correlation analysis with Chi-Square test obtained p-value 0.005 (p<0.05), education with immunization, p-value 0.017 (p<0.05), work status with immunization, p-value 0.022 (p<0 ,05). There is a relationship between maternal educational status, maternal employment status, and maternal age with immunization status.